Effectiveness of Ziswaf Fundraising Through (QRIS) in Efforts to Increase Institutional Income - Nur, Ilman; Lutfi, Muhtar; Efendi, Ahmad; Majid, Jamaluddin; Muin, Rahmawati (Jurnal Ar-Ribh, 2024)
The aim of this research is to determine the effectiveness of ZISWAF fundraising through QRIS media for the income of institutions in Wahdah, the inspiration for zakat, Makassar city. The research method used in this research uses a qualitative method using a phenomonological approach to see the phenomena that occur in institutions and society with the existence of QRIS media as a fundraising tool at Wahdah zakat inspiration. The results of the research show that collecting funds through QRIS is quite helpful in making transactions easier for people who want to pay zakat or want to donate to the Wahdah Inspiration Zakat city of Makassar. It's just that with the existence of QRIS media, there are still many people who don't trust collecting through QRIS media and don't even know how to do it. its operation. QRIS media has not had a big impact on fundraising because people who donate large amounts use mobile banking and there is a lack of funds generated through QRIS so it can be said to be ineffective.